Nutritional strategies to counter stress to the immune system in athletes, with special reference to football - Nieman, D. C.; Bishop, N. C. (Journal of Sports Sciences, 2006)
Although epidemiological data indicate that athletes are at increased risk of upper respiratory tract infection during periods of heavy training and the 1 - 2 week period following endurance race events, there is very limited information on the responses to football training and match-play. For several hours after heavy exertion, components of both the innate (e.g. natural killer cell activity and neutrophil oxidative burst activity) and adaptive (e.g. T and B cell function) immune system exhibit suppressed function. Although such responses to football training and competition do not appear to be as pronounced, variations in immune cell numbers and function are reported in professional footballers over the course of a season. Attempts have been made through nutritional means (e.g. glutamine, vitamins C and E, and carbohydrate supplementation) to attenuate immune changes following intensive exercise and thus lower the risk of upper respiratory tract infection. Carbohydrate supplementation during heavy exercise has emerged as a partial countermeasure and attenuates increases in blood neutrophil counts, stress hormones, and inflammatory cytokines, but has little effect on decrements in salivary IgA output or natural killer cell function. Animal research indicates that other nutritional components such as beta-glucan, quercetin, and curcumin warrant human investigations to determine if they are effective countermeasures to exercise-induced immune dysfunction.